Validasi Asesmen Kompetensi Kepribadian Guru: Analisis Rasch - Tb. Moh. Irma Ari Irawan; Hengki Satrianta; Hendrik Tuaputimain; Alice Asiedu; Ahman Ahman (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to validate personality competence assessment instruments for teachers with Rasch Model. This quantitative research involved 165 teachers with 72-items instrument measuring 13 dimensions of personality competence. Analysis using Winsteps 5.5.0 showed person reliability 0.83 and item reliability 0.99, indicating excellent measurement consistency. Dimensionality analysis results showed 66.1% variance explained by measurement with unexplained variance in first contrast 6.7%, meeting unidimensionality criteria. Response categories functioned optimally with ordered thresholds (-1.16, -0.46, 1.62). Of 72 items, 64 items (88.9%) showed good fit, while 8 items required revision. Findings showed “wise and prudent” dimension had highest difficulty level (3.42 logit), while “continuous professional development” lowest (-2.01 logit). This instrument provides practical contribution for teacher education institutions in evaluating teachers' personality competence objectively and evidence-based in digital era.